Henry James’s Dramas of Cultivation: Liberalism and Democracy in The Bostonians and The Princess Casamassima - Coit, E (Johns Hopkins University Press, 2015)
This article identifies an overlooked discursive context for Henry James's novels of 1886. Liberal political thought pervaded both James’s transatlantic intellectual milieu and the pages of the periodicals in which he published his work; the novels, I argue, engage critically with the democratic ideal of widespread cultivation prized by late nineteenth-century American liberalism. This engagement becomes visible only when we adopt a revised understanding of that liberalism, giving fresh attention to its overt agenda of cultivation and democracy. The novels enact the difficulties inherent in that agenda: by staging liberal cultivations that end tragically, they dramatize democratic liberalism's internal contradictions.